"That other woman–person with a broad social mission"1: historical feminism, social reform, and citizenship in Spain. Issue 1 (2nd January 2023) - Blasco Herranz, Inmaculada
ABSTRACT: This article aims to contribute to a better knowledge of historical feminism in Spain based on and in dialogue with the wealth of research on the subject by Spanish historiography in recent decades. Although the social nature of Spanish feminism and its articulation around notions of sexual difference has been pinpointed, a more profound reflection on the social nature of feminism, as well as its effects on the shaping of feminism as a social reform movement, is needed. For that purpose, this article pays attention to the epistemological framework of social duties (and rights) which became widespread in the early twentieth century. The main working hypothesis is that these notions of sexual difference were not static and that, from the second half of the nineteenth century onwards, they were given another meaning in light of the emergence of "the social" as a result of the criticism of classical liberalism's assumptions and explanations of human nature. Sexual difference was reframed through the impact of the new ideas about society, which facilitated proposals for women's public intervention in social improvement and for reshaping marriage and the domestic sphere.